A Study on the Perceptions and Attitudes of Manufacturing Engineering Technology Student’s about Student-Centred Learning - Hamzah, Khairum; Salim, Fadzilah; Miswan, Nor Hamizah; Md Johari, Md Ashadi; Waini, Iskandar; Kashi'ie, Najiyah Safwa (2014)
Student-Centred Learning (SCL) is a method of teaching that puts student at the center of the learning process. The implementation of SCL requires a shift in focus from the lecturer to the student. This method of teaching is looking suitable to the engineering technology student which focusing more on application and implementation compared to engineering student. This study investigated both perceptions and attitudes of 167 students specializing in the area of Product Design and Process Manufacturing Engineering Technology at the Faculty of Engineering Technology (FTK) in Universiti Teknikal Malaysia Melaka (UTeM). Students were given a set of questionnaires during one of the classes. From the findings, conclusion has been drawn regarding the SCL approach to support teaching and learning. The result shows that the students’ self-directed learning readiness and a positive perception toward SCL should be encouraged. At the same time, the role of lecturers is very important to ensure the successful of the SCL approach in teaching and learning is taking place and thus, will lead to a change in the perceptions and attitudes of the students towards SCL.